A systematic review of the public health risks of bioaerosols from intensive farming - Douglas,P; Robertson,S; Gay,R; Hansell,AL; Gant,TW (International Journal of Hygiene and Environmental Health, 2017)
BACKGROUND: Population growth, increasing food demands, and economic efficiency have been major driving forces behind farming intensification over recent decades. However, biological emissions (bioaerosols) from intensified livestock farming may have the potential to impact human health. Bioaerosols from intensive livestock farming have been reported to cause symptoms and/or illnesses in occupational-settings and there is concern about the potential health effects on people who live near the intensive farms. As well as adverse health effects, some potential beneficial effects have been attributed to farm exposures in early life. The aim of the study was to undertake a systematic review to evaluate potential for adverse health outcomes in populations living near intensive livestock farms. MATERIAL AND METHODS: Two electronic databases (PubMed and Scopus) and bibliographies were searched for studies reporting associations between health outcomes and bioaerosol emissions related to intensive farming published between January 1960 and April 2017, including both occupational and community studies. Two authors independently assessed studies for inclusion and extracted data. Risk of bias was assessed using a customized score. RESULTS: 38 health studies met the inclusion criteria (21 occupational and 1 community study measured bioaerosol concentrations, 16 community studies using a proxy measure for exposure). The majority of occupational studies found a negative impact on respiratory health outcomes and increases in inflammatory biomarkers among farm workers exposed to bioaerosols. Studies investigating the health of communities living near intensive farms had mixed findings. All four studies of asthma in children found increased reported asthma prevalence among children living or attending schools near an intensive farm. Papers principally investigated respiratory and immune system outcomes. CONCLUSIONS: The review indicated a potential impact of intensive farming on chil